Differences of frequencies of religious practices between catholic and evangelical/protestant in a group of elderly brazilian octogenaries - Alves, Vicente Paulo (2020)
The growth of the elderly population in Brazil allows us to make several reflections, one of them is about the relationship between health and spirituality / religiosity, mainly because we are heirs of cultural history that was inherited by Portuguese and European colonists. This study aims to verify the religious affiliation of octogenarians from the samples were for convenience and in a simple random way from a study of the elderly who sought the Geriatrics outpatient clinic at the Catholic University of Brasilia. A comparison of the responses received to the questionnaires was performed, according to socio-demographic and spirituality / religiosity variables (gender, age group, education, family income, self-rated health, practice of spirituality / religiosity). The results found show that when the aging process starts, religiosity / spirituality can be a protective factor when the losses intensify.